Performative histories, foundational fictions Anu Koivunen Finnish Literature Society · Helsinki : gender and sexuality in Niskavuori films (2003)
With these eloquent words, 1ordic 1ational Cinemas (1998) introduces the series of seven Niskavuori films (1938–1984) to an international readership. The quoted paragraphs – and the mere presence of these filmsin this particular context of packaging national cinemas into comparable products – suggest that the films in question enjoy a special status in their country of origin. What is more, the book’s description summarizes what in the Finnish context can be termed as the common sense of the Niskavuori films, pulling together several threads of their long-standing and continuing reception. First, the quote frames the films as anchored “in reality” as it connects them with the biography of the female playwright Hella Wuolijoki on whose five plays (1936–1953) the films are based.2 Wuolijoki’s persona, her family history, and political activism have always loomed large in public discourses around Niskavuori plays and films. In this quote, the biography islinked to a specific place and region, Häme (Tavastlandia), which is both the region where Hella Wuolijoki had relatives through her marriage, the narrative landscape of the Niskavuori family, and in the nationalist imaginings, a privileged locus of Finnishness since the early 19th century. Second, the quote frames the Nis kavuori films in terms of gender history, anchoring them firmly in a woman-centred and feminist point of view. In implying a parallel between the fictional world and the history of Finnish women, itreiterates another common narrative offered since the 1930s, women shouldering the household burden while men worked (in forestry, on the railroad and in log floating companies) or waged wars. An emphasis on the distinctive “power” and “strength” of Finnish women is an inherent feature of this reading. The source of this narrative – and, by implication, also the origin of a specific gender discourse featuring “strong women” and “weak men” – is located within a past, pre- modern, agrarian world. Third, the quote employs mythological language and folkloric notions of genesis in characterizing the Niskavuori women as “born out of the earth of Tavastlandia” or as “rooted in the earth”. Through these expressions, the quote enacts a reading of the films and characters as place- and soil-bound; it suggests that the representations be seen as more “authentic” or “essential”, as less mediated or fabricated than some other representations. In addition, this reading evokes a folkloric narration. It establishes links to national mythology (the Kalevala as the Finnish “national epic”) and, hence, implies that the story of the Niskavuori family not only retrieves the linear time of history, but also a mythical timelessness of repetition and monumentality. Indeed, the matrons of the Niskavuori farm are recurrently termed “monumental” and described through metaphors of trees and stones. Fourth, the quote places the Niskavuori films within the framework of melodrama and, thus, reiterates earlier readings of the Nis ka- vuo ri saga in terms of affective impact, as well as recent readings of Niska- vuori in terms of soap opera narration. Interestingly, there is no contradiction between the “realist” content (Niskavuori as history) and the melodramatic narration. In this reading, on the contrary, the melodramatic mode, i.e., the manner in which strong emotions are concealed yet visible as traces in camera movements (“scant retorts”) or “skilful mimicry” [sic] appears as an essential counterpart to the history as it is articulated in Niskavuori films. Indeed, the melodramatic mode is a key element in this image of a Finnish mentality. Fifth and lastly, as the quote does not differentiate between the Niskavuori plays and Niskavuori films, but speaks of them as one, the films are framed as inherently intertextual or, rather, intermedial. In this respect, the quote also reiterates earlier readings.